# Prove by careful induction that if $r \in \mathbb{N}$, then $b^{2^r} - 1 = (b-1)(b+1)(b^2 + 1)(b^{2^{2}} + 1) ... (b^{2^{r-1}} + 1)$

Prove by careful induction that if $r \in \mathbb{N}$, then $$b^{2^r} - 1 = (b-1)(b+1)(b^2 + 1)(b^{2^{2}} + 1) ... (b^{2^{r-1}} + 1)$$

I'm a bit rusty on Mathematical inductions, and I'm getting stuck in the process. Here's what I've tried so far:

To begin, proceed by induction on $r$

Base case: $r=1$:

$b^2 - 1 = (b-1)(b+1) = b^2 + b - b - 1 = b^2 -1$

So the base case holds.

Inductive hypothesis: the theorem holds for all $r=k$

Inductive step: let $r=k+1$

$b^{2^{k+1}} = (b-1)(b+1) ... (b^{2^{k+1-1}})$

I'm not sure this is even right so far, or where I need to go from here.

• Since this is the second time I see it in a post of yours what's the meaning or point of careful in careful induction.
– quid
Sep 8 '16 at 19:12
• Good question. Not exactly sure myself, but I think it just means to pay close attention to the steps. I don't think it means anything special like strong induction. Sep 8 '16 at 19:28

$$b^{2^k} - 1 = (b-1)(b+1)(b^2 + 1)(b^{2^{2}} + 1) ... (b^{2^{k-1}} + 1)$$ and you want to prove $$b^{2^{k+1}} - 1 = (b-1)(b+1)(b^2 + 1)(b^{2^{2}} + 1) ... (b^{2^{k-1}} + 1)(b^{2^{k}} + 1).$$
Using the inductive hypothesis, you know that the product of all but the last bracket is $b^{2^k}-1$. So it remains to check $$b^{2^{k+1}} - 1 =(b^{2^k}-1)(b^{2^k}+1)$$ which is true by difference of squares, completing the inductive step.